Management of Adult Acute Myelogenous Leukaemia. Issue 5846 (20th January 1973) - Crowther, D.; Powles, R. L.; Bateman, C. J. T.; Beard, M. E. J.; Gauci, C. L.; Wrigley, P. F. M.; Malpas, J. S.; Fairley, G. Hamilton; Scott, Ronald Bodley
Abstract : Consecutive adult patients admitted to St. Bartholomew's Hospital with acute myelogenous leukaemia have been treated with a remission induction drug schedule consisting of daunorubicin and cytosine arabinoside. Intermittent five-day courses were used in 72 patients, and a complete remission was obtained in 39 patients (54%). An alternative drug schedule in 22 patients resulted in fewer remissions but this may have been due to age differences in the two groups. Age and initial platelet count were found to be important factors in determining the success of remission induction therapy; the older patients and those with low platelet counts responded less well. A series of 23 patients who achieved remissions was divided into two groups; one received intermittent combination chemotherapy as the only form of maintenance, and the other was given weekly immunotherapy in addition to the chemotherapy. The immunotherapy consisted of irradiated allogeneic leukaemic cells and B.C.G. Eight of the 10 patients on chemotherapy alone have already relapsed compared with five out of 13 patients in the immunotherapy group. It is hoped that these promising initial results with this form of maintenance will be confirmed as more patients enter the maintenance trials.